2013
DOI: 10.2139/ssrn.2307791
|View full text |Cite
|
Sign up to set email alerts
|

It is Not Just Confusion! Strategic Uncertainty in an Experimental Asset Market

Abstract: To what extent is the observed mispricing in experimental asset markets caused by strategic uncertainty and by confusion? We address this question by comparing subjects' initial price forecasts in two market environments: one with six human traders, and the other with one human and five computer traders. We find that both strategic uncertainty and confusion contribute equally to the median initial forecast deviation from the fundamental value. The effect of strategic uncertainty is greater for subjects with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…For example, Brañas-Garza, García-Muñoz, and Hernán (2012) reported that subjects with higher scores on the Cognitive Reection Test (CRT, Frederick, 2005) choose, on average, numbers closer to the Nash equilibrium in the beauty contest games. In the same vein, Akiyama, Hanaki, and Ishikawa (2015) reported that the magnitude of the eect of strategic uncertainty is positively correlated with subjects' scores on the CRT test, while the eect of confusion is negatively correlated with the score. Burks, Carpenter, Goette, and Rustichini (2009) reported that subjects (trainee truckers) with higher scores in Raven's progressive matrix test 3 are more patient and more willing to take calculated risks.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…For example, Brañas-Garza, García-Muñoz, and Hernán (2012) reported that subjects with higher scores on the Cognitive Reection Test (CRT, Frederick, 2005) choose, on average, numbers closer to the Nash equilibrium in the beauty contest games. In the same vein, Akiyama, Hanaki, and Ishikawa (2015) reported that the magnitude of the eect of strategic uncertainty is positively correlated with subjects' scores on the CRT test, while the eect of confusion is negatively correlated with the score. Burks, Carpenter, Goette, and Rustichini (2009) reported that subjects (trainee truckers) with higher scores in Raven's progressive matrix test 3 are more patient and more willing to take calculated risks.…”
mentioning
confidence: 91%
“…Finally, Akiyama, Hanaki, and Ishikawa (2015) investigated the magnitude of the eect of strategic uncertainty in explaining the observed deviation of price forecasts from the fundamental values in an experimental asset market à la Smith, Suchanek, and Williams (1988). They found signicant eects of both confusion and strategic uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Brañas-Garza, García-Muñoz, and Hernán (2012) reported that subjects with higher scores on the Cognitive Reflection Test (CRT, Frederick, 2005) choose, on average, numbers closer to the Nash equilibrium in the beauty contest games. In the same vein, Akiyama, Hanaki, and Ishikawa (2013) reported that the magnitude of the effect of strategic uncertainty is positively correlated with subjects' scores on the CRT test, while the effect of confusion is negatively correlated with the score. Burks, Carpenter, Goette, and Rustichini (2009) reported that subjects (trainee truckers) with higher scores in Raven's progressive matrix test 3 are more patient and more willing to take calculated risks.…”
Section: Introductionmentioning
confidence: 92%
“…They found that roughly half of non-immediate adjustment to the new equilibrium after the shock was due to individual bounded rationality (or confusion) and the other half was due to strategic uncertainty. Finally, Akiyama, Hanaki, and Ishikawa (2013) investigated the magnitude of the effect of strategic uncertainty in explaining the observed deviation of price forecasts from the fundamental values in an experimental asset market à la Smith, Suchanek, and Williams (1988). They found significant effects of both confusion and strategic uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Our monopoly vs. oligopoly design is also helpful for investigating the important role played by common knowledge of rationality in eductive learning. In this respect our paper is related to other experimental studies exploring the role of common knowledge of rationality in market settings, for example, the "money illusion" experiments by Fehr and Tyran (2005, 2007 and the asset market experiments by Akiyama et al (2012Akiyama et al ( , 2013.…”
mentioning
confidence: 99%